Histology and histomorphometry of the skin in the ventral abdominal region of domestic fowl (Gallus gallus domesticus), duck (Anas platyrhynchos), and doves (Columba livia) - Zainuddin, Zainuddin; Rahmi, Erdiansyah; Akmal, Muslim; Masyitha, Dian; Ismail, Ismail; Hamny, Hamny; Pratiwi, Siska; Zulkifli, Baidillah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2024)
This study aims to determine the histological and histomorphometric characteristics of the skin of domestic fowl (Gallus gallus domesticus), ducks (Anas platyrhynchos), and doves (Columba livia) in the ventral abdominal region. Each study sample consisted of six individuals. The samples were processed into histological preparations with a thickness of 5 m and then stained using Haematoxylin-Eosin (HE). The results showed that the histological structure of the skin of domestic fowl, ducks, and doves is relatively thin compared to the structure of mammalian skin and consists of the epidermis, dermis, and hypodermis (subcutis). The histomorphometric data analysis showed that the thickness of the epidermal layer of the skin in the ventral abdominal region of domestic fowl, ducks, and doves was not significantly different (P0.05), but there were significant differences (P0.05) in the thickness of the dermis and hypodermis. It can be concluded that a similarity exists in the histological structure of the skin of domestic fowl, ducks, and doves, but differences are observed in the histomorphometric properties of the skin in the ventral abdominal region of these birds.